Finding jobs a big concern among grads - Joash EE, De Silva; Clarissa, Chung (The Star Publications (M) Berhad, 2017)
GAMBANG: Job apportunities and standardising the language medium for Science and Mathematics were among the main concerns of students at the Transformasi Nasional 50 (TN50) dialogue here.